Sonoelastography of the Shoulder: A Narrative Review - Babaei-Ghazani, Arash; Majdalani, Carl-Elie; Luong, Dien Hung; Bertrand-Grenier, Antony; Sobczak, Stéphane (Frontiers in Rehabilitation Sciences, 2021)
Sonoelastography is a relatively new non-invasive imaging tool to assess in-vivo qualitative and quantitative biomechanical properties of various tissues. Two types of sonoelastography are commonly explored: strain and shear wave. Sonoelastography can be used in multiple medical subspecialties to assess pathological tissular changes by obtaining mechanical properties, shear wave speed, and strain ratio data. Although there are various radiological imaging methods such as magnetic resonance imaging or computerized tomography scan to assess musculoskeletal structures (muscles, tendons, joint capsules), sonoelastography is more accessible since this approach is of low cost and non-radiating. As of 2018, sonoelastography has garnered promising data in multiple studies. Preliminary clinico-radiological correlations have been established in an attempt to bridge tissue biomechanical findings with their respective clinical pathologies. Specifically, concerning the shoulder complex, recent findings have described mechanical tissue changes in shoulder capsulitis. The long head of biceps and supraspinatus sonoelastography were amongst recently studied structures with regards to conditions concerning impingement, tendinosis, and tears. Since ultrasonography has established itself as an important tool in shoulder evaluation, it completes clinician’s history and physical examination skills. This paper will provide an update on the most recent findings on sonoelastography of shoulder structures.